1985
DOI: 10.1021/ja00297a044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7,9-didecarboxymethoxatin (4,5-dihydro-4,5-dioxo-1H-pyrrolo[2,3-f]quinoline-2-carboxylic acid) and comparison of its chemical properties with those of methoxatin and analogous o-quinones. Model studies directed toward the action of PQQ requiring bacterial oxidoreductases and mammalian plasma amine oxidase

Abstract: The synthesis of 4,5-dihydro-4,5-dioxo-l/f-pyrrolo[2,3-/]quinoline-2-carboxylic acid (7,9-didecarboxymethoxatin, 70X) and its ester (60X) are described and their acid-base properties, electrochemistry, and chemical properties are compared to the cofactor Methoxatin, as well as to those of other o-quinones. The two-electron redox potentials of 60x and 70x are shown to be ca. 110 mV less than those of the penanthroline-5,6-quinones but to be comparable to those of methoxatin at all pH values. Replacement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 3 publications
4
31
0
1
Order By: Relevance
“…Evidence Against Asp-297-CO 2 ؊ Being the General Base in the Oxidation of CH3OH 3 CH2O. In the 3-ns MD simulations (6,7,9) Ϫ becomes coordinated to Ca 2ϩ after Ϸ1.8 ns time (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Evidence Against Asp-297-CO 2 ؊ Being the General Base in the Oxidation of CH3OH 3 CH2O. In the 3-ns MD simulations (6,7,9) Ϫ becomes coordinated to Ca 2ϩ after Ϸ1.8 ns time (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…This MD derived structure is not in accord with the following: (i) the suggestion that Asp-297-CO 2 Ϫ serves as the general-base catalyst (14)(15)(16)(17); and (ii) that the oxidation takes place, not by hydride transfer, but by an addition elimination reaction (18,19) (Scheme 1, in which the general base may be Glu-171-CO 2 Ϫ or Asp-297-CO 2 Ϫ ). The MD studies (6,7,9) showed that Asp-297-CO 2 Ϫ is not in position to act as a generalbase catalyst for the oxidation of MeOH by MDH.…”
mentioning
confidence: 88%
See 3 more Smart Citations